Productivity and vulnerability of microcredit borrowers in microfinance: an approach using non-separability models - Ntieche Adamou,; Tourere Zenabou, (Eximia, 2024)
The aim of this paper is to find a better match between the supply of and demand for solidarity microcredit with a view to reducing the level of precariousness and vulnerability of micro-entrepreneurs. If microcredit can constitute a necessary production factor for the activity of micro-entrepreneurs, then the deployment of MFIs in developing countries to facilitate access to microfinance services for low-income agents is desirable. However, the effectiveness of such a factor requires a good analysis of the cash flow needs of micro-entrepreneurs (households) in precarious situations, which would enable financial products to be adapted. Two main lessons can be drawn from a theoretical model: (1) demand for microcredit depends not only on the cost of the service, but also on the price of the micro-entrepreneur's output, the price of labour input and the size of the business. And, although they have this labour input, micro-entrepreneurs suffer from a lack of financial means to exploit it in order to benefit from it and improve their living conditions. (2) solidarity microcredit can have a positive impact on household cash flow, improve the smoothing of their consumption and, to a certain extent, strengthen their resistance to economic shocks.